Exploring anxiety in elderly pulmonary tuberculosis inpatients using propensity score matching method - Yinping Feng; Jing Guo; Shuirong Luo; Zunjing Zhang (BMC Pulmonary Medicine)
Abstract Objective The objective of this study is to explore the factors that influence anxiety in elderly hospitalized pulmonary tuberculosis patients using propensity score matching (PSM) methods. Methods We retrospectively analyzed the clinical data of elderly patients with pulmonary tuberculosis admitted to the tuberculosis Department of Lishui Hospital of Traditional Chinese Medicine from January 2021 to October 2023. The patients were then divided into anxiety and non-anxiety groups based on their GAD-7 scores. Propensity score matching was used to match the baseline data of the two groups, followed by multivariate logistic regression analysis to identify the influencing factors of anxiety in elderly hospitalized pulmonary tuberculosis patients. Results The study included 795 elderly hospitalized patients with pulmonary tuberculosis, with 599 classified as carefree and 196 as anxious (32.72%). Using the propensity score matching method, we successfully matched 185 pairs of patients. After matching, there were no statistically significant differences in gender, age, occupation, or other aspects between the two groups of patients (all P > 0.05). Multivariate logistic regression analysis revealed that chronic comorbidities (OR = 2.36, 95% CI: 1.54–3.61), lack of daily social interaction (OR = 1.79, 95% CI: 1.15–2.76), tuberculosis recurrence (OR = 2.08, 95% CI: 1.35–3.21), and lack of daily behavioral ability (OR = 1.99, 95% CI: 1.23–3.23) were influencing factors for anxiety in elderly hospitalized pulmonary tuberculosis patients (P < 0.05). Conclusion After controlling for confounding factors through PSM, we found that chronic comorbidities, lack of daily social interaction, tuberculosis recurrence, and lack of daily behavioral ability are influencing factors for anxiety in elderly pulmonary tuberculosis inpatients. This suggests a need for clinical intervention. Clinical trial number Not applicable.